Examining the usability of e-museum search interfaces / Zafirah Ahmad Puat - Ahmad Puat, Zafirah (2009)
The purpose of this research is to examine the usability of search interface in e-museum domain. The study has three aims. Firstly, is to identify the features of search interface. When users have poorly defined or complex goal, search interface offering only keyword searching facilities provide inadequate support to help them reach their information seeking need and objectives. Hence, the identified features besides keyword search will support and help user to fulfil their, information seeking objectives. Furthermore, the second aim is to identify usability factors for evaluating the features in the e-museum search interface. However only one selected usability factors that is user satisfaction will be used to measure the features. The third aim is to identify the criteria of the key features of e-museum search interface based on user satisfaction factor. The method of this research is secondry data. The researcher use the data that are originally collected and then summarize the information according different authors. Then, the features and the criteria based on user satisfaction into selected e-museum search interface examined. The deliverables of this research is the key features of search interface, the usability factor to evaluate e-museum search interface and the criteria of features based on satisfaction factor.